2014
DOI: 10.1177/1071100714523271
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Fibular Graft Repair for the Treatment of Recurrent Peroneal Subluxation

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Eight studies reported on time to RTS, with a number of 168 included patients [ 5 , 12 , 13 , 27 , 33 , 39 , 42 , 43 ]. The time to RTS ranged from 1.2 to 12 months (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies reported on time to RTS, with a number of 168 included patients [ 5 , 12 , 13 , 27 , 33 , 39 , 42 , 43 ]. The time to RTS ranged from 1.2 to 12 months (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that flat or convex retromalleolar grooves may predispose patients to luxation of the peroneal tendons [ 14 , 32 ]. The presence of a peroneus quartus muscle or a low-lying muscle belly makes individuals also more susceptible for peroneal tendon dislocation [ 37 , 42 , 43 ]. Normal anatomy of the lateral ankle is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in magnetic resonance imaging (MRI) system have enhanced our ability to diagnose soft tissue pathologies such as tenosynovitis and tendon tear. A low lying muscle belly (Figure) is a rare anomaly, most commonly associated with peroneus brevis tendon (1–3). A low lying muscle belly is defined as a muscle extending beyond its normal length.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a peroneus brevis muscle, it is expected that the muscle would end in average 1.6–2.0 cm above the distal tip of the fibula (4). Cases of low lying peroneus brevis muscle belly (LLMB) has been documented in the literature (1, 3, 59). However, to our knowledge, association between a low lying muscle belly and tendon subluxation is not well studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation